Transient Third-Degree Atrioventricular Block in a Dog with Addisonian Crisis - Paula Maria Pașca; Gheorghe Solcan; Andrei Blageanu; Caroline Maria Lăcătuș; Petru Cosmin Peștean; Constantin Adrian Stancu; Andrei Radu Baisan (Veterinary Sciences, 2025)
A 3-year-old spayed male mixed-breed Labrador presented to the Emergency and Critical Care Unit with lethargy, loss of appetite, vomiting, a recent history of presyncopal episodes, and severe exercise intolerance. On admission, the patient had bradycardia, low blood pressure, and mild abdominal pain. Serum biochemistry information revealed severe hyperkalemia, hyponatremia, hypoglycemia, and mildly increased liver and kidney parameters. Upon taking these findings into consideration, hypoadrenocorticism was suspected, and a basal cortisol level was determined; it was below 1.0 µg/dL. Upon examination with ultrasound, we observed that the size of the adrenal glands was considerably reduced. Due to the bradycardia, a complete cardiologic examination consisting of 5 min of six-lead electrocardiography and echocardiography (ECG) was performed. Six-lead ECG revealed a complete atrio-ventricular block with an atrial rate of 140 bpm and a ventricular rate of 60 bpm. The PQ interval was variable, without any evidence of atrio-ventricular conduction. Treatment for hyperkalemia was initiated immediately after admission, followed by dexamethasone sodium phosphate administration, which led to an improvement in the patient’s general condition, and the normalization of the ECG readings, after 24 h of therapy. Afterward, prednisolone (0.5 mg/kg/24 h p.o.) and desoxycorticosterone pivalate (2.2 mg/kg s.c.) were administered. This case shows that a third-degree atrioventricular block might be a reversible problem in dogs with hypoadrecorticism that can be managed with specific treatment for this disorder, without requiring pacemaker implantation.